T & T Clark companion to the Dead Sea Scrolls - Hempel, Charlotte; Brooke, George J. (Bloomsbury companions., 2016)
This companion provides the ideal resource for those seriously engaging with the Dead Sea Scrolls. In 30 concise articles all of the key texts and documents are examined. A section on the complex methods used in anaylzing the scrolls then follows before the focus moves to consideration of the scrolls in their various contexts; political, religious, cultural, economic, historical. The genres ascribed to groups of texts within the scrolls are examined in the next section with due attention given to both past and present scholarship. The main body of the companion then concludes with crucial issues and topics discussed by leading scholars. The book finishes with appendices and indexes giving: timelines, lists of kings, family trees of the Seleucids, Ptolemies, Hasmoneans, lists of places and scrolls, information on electronic resources and classified bibliographies. The volume is illustrated throughout with some 60 images enabling readers to consider key texts from the scrolls not only in transcription but simultaneously with photographs.